Rapid assessment of the knowledge about Coleoptera (Arthropoda: Insecta) of forensic importance in an urban fragment of the Atlantic Forest in Salvador, Bahia, Brazil - Trindade-Santos, Matheus E. (2021)
Forensic Entomology can be defined as an area of Biological Sciences that uses the knowledge about insects and other Arthropods in criminal investigations, since decomposing corpses are sources of resources for arthropods, including insects belonging to the Coleoptera order. The objective of this work was to carry out a rapid assessment inventory of beetles of forensic importance in an urban fragment of the Atlantic Forest (Parque Metropolitano de Pituaçu) located in the city of Salvador, State of Bahia, Brazil. We conducted a collection in the dry period (January 2013) and another collection in the rainy period (July 2013). The capture of coleopterans took place through the use of “Pitfall” traps, stocked with a mixed bait (chicken gizzard and sardines). A total of 239 were collected, distributed in three families: Scarabaeidae (96.1%), Staphylinidae (3.0%) and Histeridae (0.9%). The morphospecies Dicothomius sp. 1 (Scarabaeidae), was more abundant with 94.1% of the specimens sampled. The dry period was more representative for both richness and abundance. All species/morphospecies sampled already have previous records as belonging to forensic importance according to previous studies.